Mechanistic insights into the ameliorative effects of hypoxia-induced myocardial injury by Corydalis yanhusuo total alkaloids: based on network pharmacology and experiment verification - Qi, Jiaying; Li, Haoying; Yang, Yakun; Sun, Xiaoqi; Wang, Jianxin; Han, Xue; Chu, Xi; Sun, Zhenqing; Chu, Li (Frontiers in Pharmacology, 2024)
Corydalis yanhusuo total alkaloids (CYTA) are the primary active ingredients in yanhusuo, known for their analgesic and cardioprotective effects. However, the mechanisms underlying the treatment of Myocardial ischemia (MI) with CYTA have not been reported. The purpose of this study was to explore the protective effect of CYTA on MI and its related mechanisms. A network pharmacology was employed to shed light on the targets and mechanisms of CYTA's action on MI. The protective effect of CYTA against hypoxia damage was evaluated in H9c2 cells. Furthermore, the effects of CYTA on L-type Ca 2+ current (ICa-L), contractile force, and Ca 2+ transient in cardiomyocytes isolated from rats were investigated using the patch clamp technique and IonOptix system. The network pharmacology revealed that CYTA could regulate oxidative stress, apoptosis, and calcium signaling. Cellular experiments demonstrated that CYTA decreased levels of CK, LDH, and MDA, as well as ROS production and Ca 2+ concentration. Additionally, CYTA improved apoptosis and increased the activities of SOD, CAT, and GSH-Px, along with the levels of ATP and Ca 2+ -ATPase content and mitochondrial membrane potential. Moreover, CYTA inhibited ICa-L, cell contraction, and Ca 2+ transient in cardiomyocytes. These findings suggest that CYTA has a protective effect on MI by inhibiting oxidative stress, mitochondrial damage, apoptosis and Ca 2+ overload. The results prove that CYTA might be a potential natural compound in the field of MI treatment, and also provide a new scientific basis for the its utilization.